#277 : Transcriptome Analysis Revealed a Delayed and Attenuated Estrogen Response in IUA Patients - Qi Guo (Fertility & Reproduction, 2023)
Background and Aims: Intrauterine adhesion (IUA) is characterized by the formation of scar tissue in the endometrium following a variety of insults such as endometrial damage, miscarriage, and infection. Despite current management with intrauterine adhesion separation and adjuvant therapies such as estrogen supplementation, a high recurrence rate and inadequate therapeutic response persist in some patients. More importantly, compromised endometrial proliferation in these patients lead to subsequent infertility. However, effective therapies to improve the impaired response to estrogen have yet to be identified. This study seeks to elucidate the molecular basis for the adverse estrogen response in IUA patients and to identify novel therapeutic targets. Method: Whole-Transcriptome sequencing: proliferative endometrium of normal and IUA patients. Results: By performing differential and enrichment analysis of transcriptomic data, we observed a considerable downregulation of estrogen-relatedgenesets in IUA patients. The expression of enhancer RNAs (eRNAs) serves as a hallmark of transcriptional activation. By identifying eRNAs in transcriptomic data and co-analyzing with ERa ChIPseq and H3K27ac ChIPseq datasets, we identified a series of downregulated eRNAs, which is mediated by estrogen. We further confirmed the downregulation of eRNAs and target genes. Interestingly, the expression of ESR1 is similar in both groups, we performed immunofluorescence analysis and demonstrated a considerable reduction of ERa-positive cells with a loss of nuclear localization in IUA. This finding provides further evidence of the insensitivity of IUA patients to estrogen and suggests a loss of estrogen genomic effects. Furthermore, we found that prolonging estrogen exposure time and increasing estrogen concentration partially enhanced estrogen effects in IUA patients, yet remained compromised, indicating the need for alternative therapeutic strategies. Conclusion: The compromised response to estrogen in IUA patients is attributed to the attenuation of estrogen receptor alpha (ERa)-mediated genomic effect.